Knowledge mapping of mitochondrial calcium uniporter from 2011 to 2022: A bibliometric analysis - Pan, Deng; Xu, Lin; Shi, Dazhuo; Guo, Ming (Frontiers in Physiology, 2023)
Background: Calcium uptake research has a long history. However, the mitochondrial calcium uniporter (MCU) protein was first discovered in 2011. As investigations of mitochondrial calcium uniporter represent a new research hotspot, a comprehensive and objective perspective of the field is lacking. Hence, this bibliometric analysis aimed to provide the current study status and trends related to mitochondrial calcium uniporter research in the past decade. Methods: Articles were acquired from the Web of Science Core Collection database. We quantified and visualized information regarding annual publications, journals, cocited journals, countries/regions, institutions, authors, and cocited authors by using CiteSpace 5.8. R3 and VOSviewer. In addition, we analysed the citation and keyword bursts related to mitochondrial calcium uniporter studies. Results: From 2011 to 2022, 1,030 articles were published by 5,050 authors from 1,145 affiliations and 62 countries or regions. The country with the most published articles was the United States. The institution with the most published articles was the University of Padua. Rosario Rizzuto published the most articles and was also the most cocited author. Cell Calcium published the largest number of articles, whereas Journal of Biological Chemistry had the most cocitations. The top 5 keywords related to pathological processes were oxidative stress, cell death, permeability transition, apoptosis, and metabolism. MICU1, calcium, ryanodine receptor, ATP synthase and cyclophilin D were the top 5 keywords related to molecules. Conclusion: mitochondrial calcium uniporter research has grown stably over the last decade. Current studies focus on the structure of the mitochondrial calcium uniporter complex and its regulatory effect on mitochondrial calcium homeostasis. In addition, the potential role of mitochondrial calcium uniporter in different diseases has been explored. Current studies mostly involve investigations of cancer and neurodegenerative diseases. Our analysis provides guidance and new insights into further mitochondrial calcium uniporter research.